A Simple and Highly Sensitive Electrochemical Biosensor for microRNA Detection Using Target‐Assisted Isothermal Exponential Amplification Reaction. Issue 10 (18th September 2013) - Yan, Yurong; Zhao, Dan; Yuan, Taixian; Hu, Jun; Zhang, Decai; Cheng, Wei; Zhang, Wei; Ding, Shijia
Abstract A simple and highly sensitive electrochemical biosensor for microRNA (miRNA) detection was successfully developed by integrating a target‐assisted isothermal exponential amplification reaction (EXPAR) with enzyme‐amplified electrochemical readout. The binding of target miRNA with the immobilized linear DNA template generated a part duplex and triggered primer extension reaction to form a double‐stranded DNA. Then one of the DNA strands was cleaved by nicking endonuclease and extended again. The short fragments with the same sequence as the target miRNA except for the replacement of uridines and ribonucleotides with thymines and deoxyribonucleotides could be displaced and released. Hybridization of these released DNA fragments with other amplification templates and their extension on the templates led to target exponential amplification. Integrating with enzyme‐amplified electrochemical readout, the electrochemical signal decreases with the increasing target microRNA concentration. The method could detect miRNA down to 98.9 fM with a linear range from 100 fM to 10 nM. The fabrication and binding processes were characterized with cyclic voltammetry and electrochemical impedance spectroscopy. The specificity of the method allowed single‐nucleotide difference between miRNA family members to be discriminated. The established biosensor displayed excellent analytical performance toward miRNA detection and might present a powerful and convenient tool for biomedical research and clinic diagnostic application.